2008
DOI: 10.1056/nejmoa074306
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and Treatment Outcome in Cytogenetically Normal Acute Myeloid Leukemia

Abstract: Genotypes defined by the mutational status of NPM1, FLT3, CEBPA, and MLL are associated with the outcome of treatment for patients with cytogenetically normal AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

49
1,190
17
28

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,487 publications
(1,284 citation statements)
references
References 40 publications
49
1,190
17
28
Order By: Relevance
“…Subsequently, patients suffering from AML develop symptoms attributed to granulocytopenia, anaemia, and thrombocytopenia [2]. Besides age, cytogenetic and molecular features are the main prognostic factors that influence survival [3,4]. Hence, in 2009 the European LeukemiaNet (ELN) proposed a standardized reporting system that risk stratifies patients according to their genetic subgroup.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, patients suffering from AML develop symptoms attributed to granulocytopenia, anaemia, and thrombocytopenia [2]. Besides age, cytogenetic and molecular features are the main prognostic factors that influence survival [3,4]. Hence, in 2009 the European LeukemiaNet (ELN) proposed a standardized reporting system that risk stratifies patients according to their genetic subgroup.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in 2009 the European LeukemiaNet (ELN) proposed a standardized reporting system that risk stratifies patients according to their genetic subgroup. As of today, it is well established for early prognostic assessment in AML patients [5,4,6,7,3,[8][9][10]. Thus, patients in this cohort were primarily grouped according to these criteria [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in NPM1 are the most commonly observed gene abnormalities in patients with AML, occurring in B50% of patients. 41 Patients with an NPM1 mutation and wild-type FLT3 have the highest likelihood of long-term relapse-free, event-free and OS vs all other patients. 43 However, NPM1 mutations predict better outcomes only in the absence of FLT3-ITD.…”
Section: Flt3 As a Prognostic Markermentioning
confidence: 96%
“…32,39 Mutations in the tyrosine kinase domain of FLT3 frequently occur in patients with prognostically favorable NPM1 mutations, which further complicates analyses of their impact on patient outcomes. 40,41 In fact, a study of 1107 adult patients with AML showed improved survival in patients with FLT3 tyrosine kinase domain mutations vs patients with wild-type FLT3. 42 Frequently, patients with AML have mutations in more than one gene, further complicating prediction of their prognoses.…”
Section: Flt3 As a Prognostic Markermentioning
confidence: 99%
“…Patients with FLT3 internal tandem duplication (ITD)-negative and NPM1-mutated AML have a favorable prognosis; those with FLT3-ITD mutations have a poor prognosis [30], essentially among patients with normal karyotype [28]. Patients with AML, diploid karyotype, and bi-allelic CEBPa mutations (2% or less of AML) also have a favorable prognosis [6].…”
mentioning
confidence: 99%